Основні поняття системи автоматизованого керування технологічними процесами у будівельній галузі - Шатров, С. В. (Ways to Improve Construction Efficiency, 2012)
The questions of article contains the basic concepts of automatic control systems of technological processes and the use of such systems in the construction industry.